Implementasi Link State Routing Dengan Algoritma Dijkstra Pada Jaringan GM Purinet Kosambi Menggunakan Metode NDLC - Firdiansyah, Adri; Carudin, C; Purnamasari, Intan (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
The growth of Startup companies is soaring in this era of digital economy, not a few also use LAN within the scope of their company to conduct data transactions between divisions in the company. This study aims to analyze the performance of the Link State routing protocol with Dijkstra's Algorithm using qualitative method and the Network Development Life Cycle (NDLC) methodology. Qualitative method aims to test the quality of a system to assess its performance. The research object that will be selected is GM Purinet Kosambi for the reason it has all the requirement needed for this research to continue. Because the performance of Link State Routing is not yet known by many people if it is implemented and used as a superior routing protocol in a Startup business that uses a Computer Network in it, the author is interested in researching it. The results of this study indicate that the performance of Link State Routing is very good according to the parameter of Quality of Service (QOS) and can prevent and solve existing problems as well as preventable problems such as network disconnections and detection of disturbances that commonly occur in computer networks.